2000
DOI: 10.1159/000028356
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive/Anti-Edema Effects of Liposomal Morphine during Acute Inflammation of the Rat Paw

Abstract: We evaluated the anti-edema/antinociceptive effects of subcutaneous free and liposomal morphine in rats with carrageenan-induced inflammation of the paw. We assessed antinociception by the paw pressure test and edema by plethysmography. Unilamellar liposomes (150–200 nm) with 0.3% morphine hydrochloride were used; encapsulation signifcantly reduced the rate for release of morphine in vitro. During inflammation, the antinociceptive potency of free, but not liposomal morphine increased 2.5 times; moreover, durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In our model (Larson et al, 1986), CFA injection induced a local inflammatory response with decreased nociceptive thresholds and increased plasma extravasation that was observed 4 h after CFA and that lasted 14 days. Most studies have shown that local inflammation increases opioid potency after intraplantar injection (Stein et al, 1988;Perrot et al, 2001), whereas only a few observed increased morphine potency after systemic administration (Planas et al, 2000). In our study, morphine was injected subcutaneously, and we could demonstrate that its antihyperalgesic effects were significantly greater in the inflamed than in the contralateral paw, whereas the antiallodynic effects were similar in both paws.…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365supporting
confidence: 41%
See 1 more Smart Citation
“…In our model (Larson et al, 1986), CFA injection induced a local inflammatory response with decreased nociceptive thresholds and increased plasma extravasation that was observed 4 h after CFA and that lasted 14 days. Most studies have shown that local inflammation increases opioid potency after intraplantar injection (Stein et al, 1988;Perrot et al, 2001), whereas only a few observed increased morphine potency after systemic administration (Planas et al, 2000). In our study, morphine was injected subcutaneously, and we could demonstrate that its antihyperalgesic effects were significantly greater in the inflamed than in the contralateral paw, whereas the antiallodynic effects were similar in both paws.…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365supporting
confidence: 41%
“…which time opioid release could be of a lesser magnitude than in earlier phases of inflammation, when the pronociceptive effects of the antagonists have been demonstrated (Planas et al, 2000;Stein et al, 2001b).…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365mentioning
confidence: 98%
“…Therefore, it is suggested that the mechanism of action of CHAE may be related to prostaglandin synthesis inhibition, as described for the anti-inflammatory mechanism of indomethacin in the inhibition of the inflammatory process induced by carrageenan (Di Rosa et al, 1971). In addition, the classification of antinociceptive drugs is usually based on their mechanism of action either on the central nervous system or on the peripheral nervous system (Planas et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that opiates exhibit antiinflammatory properties [12][13][14]. In particular, it has been demonstrated that in the analgesic dose range, morphine produced a reduction in carrageenan-induced hyperthermia and oedema, indicating that it reduces vascular signs of inflammation (vasodilatation and vascular permeability) in addition to inhibition of hyperalgesia [12].…”
Section: Discussionmentioning
confidence: 99%